Ameliorative effects of coriander extract supplementation in mitigating nickel toxicity in grass carp (Ctenopharyngodon idella) - Syed Muhammad Farhan Ali Shah; Syed Makhdoom Hussain; Weifang Wang; Khalid A. Al-Ghanim; Nadia Nazish (Scientific Reports)
Abstract This research explored the ameliorative effects of coriander (Coriandrum sativum) seed extract supplementation in mitigating nickel (Ni) toxicity in fish. For this purpose, Ctenopharyngodon idella fingerlings (average weight: 12.35 ± 0.04 g/fish) were randomly assigned to 18 tanks, divided into six groups with three replicates each. The six treatments were categorized as follows: the negative control group (NC) received no supplement and no Ni exposure, while the positive control group (PC) was exposed to 3.6 mg/L Ni without supplementation. The remaining four groups were fed dietary supplements with 1%, 2%, 3%, and 4% C. sativum, respectively, and were exposed to 3.6 mg/L Ni. Over the next 60 days, the trial continued. Waterborne Ni negatively impacted fish growth performance, blood profile, body composition, and antioxidant activity of C. idella. On the other hand, dietary C. sativum improved fish health and successfully reduced Ni toxic potential. Notably, 1% C. sativum supplementation enhanced growth performance (weight gain: 22.82 g; weight gain percentage: 185.74%) and improved carcass quality (protein: 14.65%; fat: 4.15%; ash: 2.74%; moisture: 74.84%). Additionally, it improved blood indices (RBCs: 2.45 × 106 mm−3; WBCs: 14.21 × 103 mm−3) and antioxidant activity (SOD: 30.26 U/mg; CAT: 3.66 U/mg; GST: 48.35 U/mg), significantly improving serum biochemical indices and mitigating Ni toxicity. In summary, the results suggest that dietary supplementation with 1% C. sativum effectively reduces Ni toxicity in C. idella.